Enhancing Operational Performance through Psychological Safety and Followership: A Case Study of Casual Workers at CV. Adik Wijaya - Bernadine Charis Adika Purna (Journal of Economics and Business UBS, 2026)
The Indonesian labor market is characterized by a significant informal sector, where approximately 60% of the workforce operates without formal contracts, particularly in the SME sector. This study addresses a "Human Capital Paradox" at CV. Adik Wijaya Rice Mill, a family-owned SME in Subang, where a reliance on casual workers often leads to operational integrity issues, such as data falsification and defensive silence due to a lack of psychological safety. Using a qualitative case study approach with the "Five Whys" methodology and Kelley’s Followership Model, the research investigated how behavioral interventions can transform "Passive" or "Pragmatic" followers into "Exemplary" partners. Findings indicate that current operational inconsistencies are driven by a rational fear of punitive management rather than technical incompetence. The implementation of coaching-based leadership and structured daily check-ins successfully reduced the interpersonal cost of speaking up, fostering a "Safe-Learning" environment. Results show that when relational governance replaces rigid command-and-control tactics, informal workers exhibit higher loyalty, proactive engagement, and improved data transparency. This research provides a scalable blueprint for Indonesian SMEs to optimize their informal workforce by prioritizing psychological contracts over formal legal agreements to achieve sustainable operational excellence